2004
DOI: 10.1016/j.immuni.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-Induced Increase in T Cell Size Involves PKC and NFAT Activation of Rel/NF-κB-Dependent c-myc Expression

Abstract: Cell growth during the G1 stage of the cell cycle is partly controlled by inducing c-myc expression, which in B cells is regulated by the NF-kappaB1 and c-Rel transcription factors. Here, we show that c-myc-dependent growth during T cell activation requires c-Rel and RelA and that blocking this growth by inhibiting protein kinase C theta (PKCtheta) coincides with a failure to upregulate c-myc due to impaired RelA nuclear import and inhibition of NFAT-dependent c-rel transcription. These results demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 45 publications
5
90
0
Order By: Relevance
“…It was shown that growth and proliferation of activated T cells requires induction of c-Myc by Rel/NF-B activity. This process depends on protein kinase C (PKC )-controlled nuclear translocation of c-Rel and AP-1/NFATinduced transcription of RelA (30). Based on the resemblance between iNKT cell development and activation of conventional T cells, it is tempting to speculate that this mechanism is also involved in iNKT development.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that growth and proliferation of activated T cells requires induction of c-Myc by Rel/NF-B activity. This process depends on protein kinase C (PKC )-controlled nuclear translocation of c-Rel and AP-1/NFATinduced transcription of RelA (30). Based on the resemblance between iNKT cell development and activation of conventional T cells, it is tempting to speculate that this mechanism is also involved in iNKT development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a mild learning deficit (Meffert and Baltimore, 2005), loss of NF-kB p50/p105 function is associated with defects in stress responses, Hu et al (1999), Li et al (1999a), Takeda Grumont et al (1998Grumont et al ( , 1999, Cheng et al (2003), Pohl et al (2002) T cells: defects in CD4 and CD8 T-cell responses, Th1 development and cytokine production (IL-2 and GM-CSF) in CD4 + T-cell responses Hilliard et al (2002), Lamhamedi-Cherradi et al (2003), Mason et al (2004), Gerondakis et al (1996), Rao et al (2003) Horwitz et al (1997) rela À/À c-rel À/À Yes (BE13) Multiple hemopoietic defects. Radiation chimeras exhibit nucleated erythrocytes, reduced number of B cells, systemic expansion of granulocytes and a reduction in monocytes Grossmann et al (1999Grossmann et al ( , 2000 T cells exhibit a cell-cycle block early in G1 resulting from a failure to undergo c-Myc-dependent growth Grumont et al (2004) rela À/À c-rel À/ À tnf À/À Neonatal E18 embryos exhibit multiple epidermal defects that include a failure to form specific hair types, disorganized basal Gugasyan et al (2004) Knockout and transgenic models for NF-jB pathway S Gerondakis et al plus impaired innate and adaptive immune function. Ascribing the defects observed in nfkb1 À/À mice solely to a loss of p50 function is complicated by the finding that approximately one-third of the p105 pool acts as a scaffold for the MEK kinase Tpl2 (Beinke and Ley, 2004).…”
Section: Nf-kb P50/p105mentioning
confidence: 99%
“…All mice were inbred C57BL/6. Mice were genotyped by PCR as previously described (15). Mice were housed in a sterile, pathogen-free environment.…”
Section: Deletion Of Mnt In T Cells To Delete Mnt In T Cells Mntmentioning
confidence: 99%
“…This inability of c-Myc-deficient T cells to differentiate past DN stages may be linked to an important role for c-Myc in proliferation mediated by pre-TCR signaling (54). Further, in naive quiescent peripheral T cells, c-Myc is downregulated, perhaps by a dedicated pathway (4), but then again upregulated as part of the proliferative response mediated by antigen-mediated TCR activation (15).…”
mentioning
confidence: 99%